Is Average Worrying? A Mixed Method Study of Malaysian Public University Administrative Staff’s Workplace Communication Apprehension - Mohd Zulfadli, Mat Husin; Nor Yazi, Khamis (Universiti Teknologi Malaysia, 2023)
Even when employed, English oral communication skills proficiency continues to be an asset; mastering the skill is advantageous. The notion has driven comprehensive studies on communication, including apprehension, yet the focus on workplace contexts remainsminimal. Therefore, this investigation aims to discern communication apprehension’s effect on staff’s communication skills, their administrative tasks, and the institution, to support the skill enhancement. Utilizing the Personal Report of Communication Apprehension instrument and a purposive sampling, the study’s explanatory sequential mixed method design sampled institution’s one hundred fifteen administrative staff. The staff communication apprehension levels were recorded as moderate, with the highestin delivering public speeches. Nevertheless, interview results proved differently to extend worrying trends among staff. The trend could jeopardize staff’s personality and productivity in the long run. The mediocre level also hinted at skill’s stagnant inclination or deterioration if itis not consistently used in conducting workplace tasks or events.The need for an impactful lifelong learning professional development plan to improve staff English oral communication skills is apparent by the University. The university's plan also need to include supporting sustained, inclusive, and sustainable economicgrowth, full and productive employment, and decent work for their employees